Social Enterprise Communication Management Tab Space in Supporting Disabled Artists - Nayla Ramadhanisa; Lusy Mukhlisiana (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Artists with disabilities often face limited access and information in promoting their work. Tab Space, a studio based in Bandung, takes on the role of a social enterprise that supports artists with disabilities through art and creative products. This study aims to explore how Tab Space manages its communication strategies in supporting artists with disabilities. Using a qualitative approach with a case study method and an interpretive paradigm, data were collected through in-depth interviews, observations, and documentation. Informants included the board of directors, Art facilitators, artists with disabilities, and expert informants. The findings reveal that Tab Space’s communication management is based on three main pillars: consistency, innovation, and collaboration. The consistency pillar is reflected in ongoing internal support for the creative process. Innovation is demonstrated through the adaptation of artworks into commercial products such as merchandise. Meanwhile, collaboration is established through partnerships with various external parties to expand reach and social impact. The study also identified communication barriers, both internal and external, which can potentially hinder the effectiveness of communication management. These findings highlight the importance of communication that is well-directed, responsive, and inclusive, to keep Tab Space a productive and sustainable space for artists with disabilities.